Migration of the population in Tuva according to the All-Russian Census of 2020 - Abylkalikov, Salavat I.; Baimurzina, Guzel R.; Batalov, Roman O. (The New Research of Tuva, 2023)
The article analyzes migration processes in the Republic of Tuva using the data of the All-Russian Population Census of 2020 (the Russian Census of 2020) that was conducted in the fall of 2021. The authors consider the main characteristics of migration cohorts, such as place of birth and features of lifelong migration of the population, duration of residence and acclimation of people to places they move in, issues of registration in places of residence and stay, characteristics of persons temporarily staying in the country, as well as problems of the quality of statistics related to the Russian Census of 2020 at the regional level. The results of the study have shown that in the inter-census period the number of natives of other regions of Russia decreased in the Republic of Tuva, and the number of visitors from other countries, including Kyrgyzstan, Kazakhstan and China, increased. The majority of the population have permanent registration at their place of residence, but the proportion of people without permanent registration is significantly higher in Tuvan towns than in rural areas, especially among young people. More than half of the residents of Tuva who indicated the duration of their residence had no experience of long-term migration, especially among rural population. The proportion of new settlers in urban areas is higher than in rural territories. This is a consequence of the ongoing urbanization of the region. The study has revealed that despite the shortcomings, the 2020 population census has allowed to obtain information about migration from a different angle, rather than the traditionally used data from the continuous survey, and to collect unique data on small population groups, including those with migration experience.